2008
DOI: 10.1146/annurev.phyto.45.062806.094406
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Ceratocystis fagacearum, the Oak Wilt Fungus

Abstract: The oak wilt pathogen, Ceratocystis fagacearum, may be another example of a damaging, exotic species in forest ecosystems in the United States. Though C. fagacearum has received much research attention, the origin of the fungus is unknown. The pathogen may have been endemic at a low incidence until increased disturbances, changes in land use, and forest management created conditions favorable for disease epidemics. The host genus Quercus contains some relatively resistant species native to the United States, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 38 publications
0
55
0
1
Order By: Relevance
“…During the course of the past approximately 60 years, the name Ceratocystis fagacearum has also been adopted by plant pathologists and mycologists working on all aspects of the important disease known as oak wilt and the biology of the fungus (e.g. Shigo 1958, Cobb et al 1965, Peplinksi and Merrill 1974, Gibbs and French 1980, Juzwik and French 1983, Appel et al 1990, Kile 1993, Gibbs 2003, Juzwik et al 2008, 2011. A search on 26 August 2017 for C. fagacearum in Google Scholar and Google respectively yielded 1940 and 119000 hits, while the name Ch.…”
Section: Mycobank Mb822520mentioning
confidence: 99%
See 1 more Smart Citation
“…During the course of the past approximately 60 years, the name Ceratocystis fagacearum has also been adopted by plant pathologists and mycologists working on all aspects of the important disease known as oak wilt and the biology of the fungus (e.g. Shigo 1958, Cobb et al 1965, Peplinksi and Merrill 1974, Gibbs and French 1980, Juzwik and French 1983, Appel et al 1990, Kile 1993, Gibbs 2003, Juzwik et al 2008, 2011. A search on 26 August 2017 for C. fagacearum in Google Scholar and Google respectively yielded 1940 and 119000 hits, while the name Ch.…”
Section: Mycobank Mb822520mentioning
confidence: 99%
“…Oak wilt is caused by a fungus in the genus Ceratocystis, which is widely known as Ceratocystis fagacearum (Juzwik et al 2008, 2011, Harrington 2009). The genus was originally described to accommodate the sweet potato pathogen, C. fimbriata (Halsted 1890).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the pathogen species and the host, plants may become stunted, wilt partially or completely, and ultimately die. Plant death may occur within days to weeks or, in case of perennials, months to years (Purcell and Hopkins, 1996; Fradin and Thomma, 2006; Niño-Liu et al, 2006; Juzwik et al, 2008; Klosterman et al, 2009, 2011; Michielse and Rep, 2009; Genin, 2010; Janse and Obradovic, 2010; Harwood et al, 2011). Age, fitness, and the nutritional status of the host, environmental conditions, and virulence of the pathogen can all determine the speed and severity at which symptoms develop (Tjamos and Beckman, 1989; Hayward, 1991; Roncero et al, 2003; Niño-Liu et al, 2006; Chatterjee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Vascular wilt pathogens generally overwinter in soil, plant debris, watercourses, or in insect vectors (Fradin and Thomma, 2006; Niño-Liu et al, 2006; Juzwik et al, 2008; Klosterman et al, 2009,2011; Michielse and Rep, 2009; Genin, 2010; Janse and Obradovic, 2010; Nadarasah and Stavrinides, 2011). While most vascular wilt pathogens are soil-borne and enter their hosts through the roots by penetration via wounds or cracks that appear at the sites of lateral root formation (Vicente et al, 2001; Di Pietro et al, 2003; Fradin and Thomma, 2006; Klosterman et al, 2009; Michielse and Rep, 2009; Genin, 2010), some enter leaves via natural openings such as stomata and hydathodes, such as the bacterial leaf blight pathogen of rice, Xanthomonas oryzae (Niño-Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Geldenhuis et al 2004;Roux et al 2004Roux et al , 2007Tarigan et al 2010) have confirmed the ability of these fungi to infect trees through these wounds. In general, natural infections might be the result of wind or rain splash dispersal of spores, or by transmission of inoculum by arthropod vectors such as bark beetles, nitidulid beetles and mites (Malloch and Blackwell 1993;Six 2003;Klepzig and Six 2004;Hayslett et al 2008;Juzwik et al 2008). The avoidance of wounds is, therefore, a key management recommendation to reduce the impact of wood stain and disease caused by these fungi in fruit orchards, plantations and ornamental trees.…”
Section: Introductionmentioning
confidence: 99%